Role of MicroRNA-155 as a Potential Biomarker for Allergic Rhinitis in Children - Noha M. Hammad; Fedaa Nabil; Eman M. Elbehedy; Randa Sedeek; Magdy I. Gouda; Mohamed A. Arafa; Saffaa M. Elalawi; Alia A. El Shahawy (Canadian Respiratory Journal)
Background. Allergic rhinitis (AR) is an inflammatory state categorized by a disturbance of immunoregulatory mechanisms. MicroRNA-155 (miRNA-155) has an essential role in regulating gene expression and can mediate the allergic TH2 process. Objective. In this study, we aimed to evaluate the role of miR-155 as a biomarker in AR and correlate its level with the total nasal symptom score (TNSS) and the levels of serum interleukin-4 (IL-4). Methods. This study included 90 children: 45 with pollen-induced AR and 45 healthy controls. Serum miR-155 expression levels were measured using quantitative real-time PCR. Human IL-4 ELIZA kits were used for the semiquantitative detection of the serum levels of IL-4. Receiver operating characteristic (ROC) curves were used to determine the best cutoff values for the studied parameters for the diagnosis of AR. Results. The demographic characteristics of the two groups were matched with respect to age and sex. The AR case group included 23 (51.1%) males and 22 (48.9%) females, while the control group included 24 (53.3%) males and 21 (46.7%) females. The miR-155 level was increased in the serum of children with pollen-induced AR compared with controls (mean difference = 2.8, p<0.001). A significant positive correlation between the serum expression level of miR-155 and TNSS in children with AR was detected (r = 0.494, p<0.001). However, no significant correlation was identified between the expression of miR-155 and that of IL-4. At a cutoff value of 1.09, the sensitivity of miR-155 as a biomarker for AR was 100%, and the specificity was 71.1%. Conclusion. MiR-155 expression levels were elevated in the serum of AR children. Therefore, miR-155 could be used as a biomarker in AR diagnosis.